2017
DOI: 10.5423/ppj.oa.03.2017.0046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Rosellinia necatrix Transcriptome and Genes Related to Pathogenesis by Single-Molecule mRNA Sequencing

Abstract: White root rot disease, caused by the pathogen Rosellinia necatrix, is one of the world’s most devastating plant fungal diseases and affects several commercially important species of fruit trees and crops. Recent global outbreaks of R. necatrix and advances in molecular techniques have both increased interest in this pathogen. However, the lack of information regarding the genomic structure and transcriptome of R. necatrix has been a barrier to the progress of functional genomic research and the control of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
5
7
0
Order By: Relevance
“…The number of predicted genes (12,104) obtained in this study is congruent with data from previous transcriptomes from R. necatrix (10,616 [12];), as well as other plant pathogenic Ascomycota, such as Fusarium graminearum (13,332 genes [22];), Valsa mali (13,046 genes [11];), or Magnaporte oryzae (11,101 genes [23];). When comparing gene expression profiles between R. necatrix infecting avocado roots or growing on PDA medium, a number of transcripts were related with major fungal traits involved in the interaction with the host, among others, CWDE [24], production of toxic compounds and detoxification of those produced by the host, or potential effectors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The number of predicted genes (12,104) obtained in this study is congruent with data from previous transcriptomes from R. necatrix (10,616 [12];), as well as other plant pathogenic Ascomycota, such as Fusarium graminearum (13,332 genes [22];), Valsa mali (13,046 genes [11];), or Magnaporte oryzae (11,101 genes [23];). When comparing gene expression profiles between R. necatrix infecting avocado roots or growing on PDA medium, a number of transcripts were related with major fungal traits involved in the interaction with the host, among others, CWDE [24], production of toxic compounds and detoxification of those produced by the host, or potential effectors.…”
Section: Discussionsupporting
confidence: 86%
“…Transcriptome analysis of R. necatrix strains growing on rich medium, has recently been addressed as an alternative to provide insights into plant pathogenicity mechanisms used by this ascomycete [12, 13]. However, neither of the two studies was carried out using R. necatrix directly interacting with a host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis has recently been addressed as an alternative to provide insights into plant pathogenicity mechanisms used by R. necatrix [12,13]. However, neither of the two studies was carried out using R. necatrix directly interacting with a host.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome analysis of the hypovirulent strain W97, infected with the megabirnavirus 1 (RNmbv1), revealed that primary and secondary metabolism, as well as genes encoding transcriptional regulators, plant cell walldegradating enzymes (CWDE), and toxin production such as cytochalasin E, were greatly disturbed in the hypovirulent strain. In another study, the transcriptome analysis of the virulent R. necatrix strain (KACC40445) identified 10,616 full-length transcripts among which, pathogen related effectors and CWDE encoding genes were predicted [12]. Data presented in both transcriptomics studies are a analysis was also applied to the Top 100 over-expressed genes (Fig.…”
Section: Introductionmentioning
confidence: 99%